Validity and reliability of the Korean version of the Digital Burnout Scale - Choi, Seung-Yi; Kim, Jung-Hee (Frontiers in Public Health, 2024)
Objectives To investigate the factor structure and verify the validity and reliability of the Korean version of the Digital Burnout Scale (DBS) among Generation Z university students. Methodology The World Health Organization guidelines were employed in the forward and back translation, synthesis, cross-cultural adaptation, and pre-survey phases to result in the Korean version of the DBS. The Korean version was then used to collect data from 330 university students online. Construct, convergent, discriminant, and concurrent validity, and internal consistency were assessed. Findings The Korean version of the DBS had three subscales (digital aging, digital deprivation, and emotional exhaustion) and included 24 items. The results of the confirmatory factor analysis indicated adequate model fit indices. Convergent, discriminant, and concurrent validity were satisfactory. The Cronbach’s ⍺ for the overall scale was 0.95. Conclusion The Korean version of the DBS has good reliability and validity and can be used as a tool to assess the level of risk of digital burnout and provide appropriate support and intervention. Implications The Korean version of the DBS will serve as a framework for developing healthy digital education by grasping individual characteristics. Longitudinal research is recommended to identify factors that cause digital usage and burnout for various age groups.